STRATEGIC TRIAD OF SECURITY AND DEVELOPMENT: THE ROLE OF CORPORATE CULTURE, COMMUNICATIONS AND PERSONAL BRANDING IN ENSURING THE RESOURCE SUSTAINABILITY OF AN ENTERPRISE - BAHAN, Nadiia; BOHDANOVA, Valeriia; HUNKO, Anhelina; STARENKYI, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the concept of the strategic triad of security and development of an enterprise, which integrates corporate culture, communications, and personal branding as interrelated strategic components that determine the enterprise’s resource sustainability and capacity for long-term growth. The research substantiates that the synergy between these three elements forms a stable foundation for enhancing the organization’s adaptive potential, innovation activity, and competitiveness under conditions of economic turbulence and digital transformation. Corporate culture is defined as a system of shared values, beliefs, and behavioral models that unite employees and determine managerial efficiency, internal stability, and organizational integrity. It ensures the coherence of actions, creates an atmosphere of trust, and fosters social responsibility within the enterprise. Communications are explored as a key management mechanism that guarantees transparency, coordination, motivation, and effective decision-making. In the context of digitalization, internal and external communications serve as vital tools for maintaining information security, improving corporate reputation, and building sustainable stakeholder relationships. Personal branding is analyzed as a strategic component of the enterprise’s reputational and human capital. It enhances the visibility and credibility of the organization through the professional authority of its leaders and experts, strengthens the employer brand, and contributes to the attraction and retention of talented employees. The research demonstrates that a well-developed system of personal branding not only increases external recognition but also supports innovation and internal motivation among personnel. The integration of corporate culture, communications, and personal branding creates a comprehensive management framework that promotes resilience, strategic flexibility, and sustainable development. The findings of this study can be applied to improve corporate governance strategies, human resource management practices, and organizational security systems, providing enterprises with a competitive advantage and long-term viability in a dynamic business environment.
Keywords: communication; corporate culture; personnel security; resource security; self-brand